Phospholipid supplementation inhibits male and female odor discrimination in mice - Morozova, Maryana; Andrejeva, Jelizaveta; Snytnikova, Olga; Boldyreva, Lidiya; Tsentalovich, Yuri; Kozhevnikova, Elena (Frontiers in Behavioral Neuroscience, 2024)
The dietary phospholipids (PL) are the promising supplements are that are commonly found as natural food ingredients and as emulsifier additives. The present study aimed at evaluating the effect of major PL found as food supplements on social behavior in mice. Here, the effect of short-term high dietary PL content was studied in terms of social odor discrimination and social interactions with male and female intruders in male mice. We used odor discrimination and habituation tests to demonstrate that PL-fed male mice tend to lose preference toward female odor and fail to discriminate socially significant scents. At the same time, test animals recognize non-social odors. We also found that PL affected social behavior of the test males, tending to behave indiscriminately toward male and female intruders during direct contact. Brain metabolomic profiling revealed no major changes in the intermediary metabolism and neurotransmitter biosynthesis. At the same time, intranasal PL application resembled the effects of dietary supplementation. These data suggest that certain PL might act as suppressors of pheromone perception in the olfactory system and affect sensing socially important odor cues.